Food security and poverty reduction programmes: the experience of female headed households in a Cape Town community - Duncan, Sarah (Department of Environmental and Geographical Science, 2017)
Living in impoverished urban areas, female headed households are most vulnerable to food insecurity. In order to reduce the risk and abate the experience of household food insecurity, civil society (NGO) and government have established numerous poverty reduction programmes and initiatives. However, in spite of ongoing efforts, the proportion of South African households experiencing food insecurity has not decreased but rather plateaued (SANHANES-1, Shisana et al, 2013). In order to address this plateau, the research has answered the question - how do food insecure female headed households experience the contributions of poverty reduction programmes in meeting their food security needs? The purpose of the study has been to add to relevant literature, with the aim of describing what food insecure households consider the contribution of poverty reduction programmes to be in meeting their food security needs. The research had four objectives - to describe (1) what food insecure households believe food in/security is, (2) how food insecure households experience food insecurity, (3) the characteristics of effective poverty reduction programmes from the perspective of food insecure households, and (4) the characteristics of ineffective poverty reduction programmes from the perspective of food insecure households. A descriptive qualitative methodology was used with data gathered through the methods of Photovoice with photo-elicitation interviews, semi-structured interviews, collage, observation field notes and a self-constructed questionnaire. The research participants, five female heads of households, were purposively sampled from a low-income Cape Town community. The research found that participant's food insecurity could not be separated from their lived experience of poverty. Making use of and influenced by Internal and External Drivers, participants were found to actively engage their living conditions with the use of social networks to be of particular importance. Participants experienced the contributions of programmes as 'half a help'. While programmes did help the participants and their households, that help served to only sustain rather than uplift them out of poverty and towards food security. If the plateau is to be addressed, then this study has argued that local programmes need to better engage their users and join with other multi-scale actors to form integrated poverty reduction programmes which offer more comprehensive, collaborative and dynamic approaches to the realization of household food security in South Africa.